Nonlinearity of Conductor Behavior in the Context of Loads on Transmission Towers - WANDZIK Grzegorz; KOWALCZYK Grzegorz (Architecture, Civil Engineering, Environment)
The article presents the issue of determining the effects of conductors on the supporting structures of power lines using two different methods of applying partial safety factors (PSF). An assessment of the nonlinearity and disproportionality in the relationship between the conductor load and the tension force was carried out. The discussion identifies the source of differences in the approaches and assesses the impact of two primary factors: the curvature of the relationship between load and tension force, and the initial prestressing of the cable, which results in the displacement of the graph relative to the origin of the coordinate system. The investigation utilizes measures of nonlinearity to facilitate its assessment. A sensitivity analysis was performed to examine the difference between applying PSFs to actions and their effects. A series of numerical calculations, considering various spans, initial tensions, and load values, demonstrated the scale of the reduction in the design values of forces when safety factors are applied more naturally to the actions, not to their effects.